Agustín Salucio's Rehabilitation of the converso and the Revisionist Debate over Racial and Religious Discrimination in Early Seventeenth-Century Spain*. Issue 10 (26th November 2017) - Rawlings, Helen
Abstract: At the beginning of the seventeenth century an unprecedented debate took place within Spanish society on the continued validity of the test of limpieza de sangre —a discriminatory code that prevented those of non-Christian ancestry from gaining access to social and professional honours. The instigator of the debate was the Dominican friar, Agustín Salucio, who in his Discurso acerca de los estatutos de limpieza de sangre (1599) advocated a fundamental relaxation of the purity of blood statutes and the rehabilitation of the converso . In doing so, he overturned the deep-rooted prejudices that had been held towards converted Jews for generations, endorsed in the procedures of the Inquisition itself, and mounted an audacious challenge to the operation of racial and religious exclusion in society. Salucio's paper prompted numerous responses penned by parliamentary deputies, government ministers, inquisitors, political theorists and fellow theologians that generated a radical review of the whole value system of early modern Spain, based on faith and lineage. This essay will engage in a close study of this far-reaching revisionist discourse that shook the orthodox foundations of the body politic and shaped the wider reform agenda of the monarchy.